Connecting Indigenous Knowledge of Keris with Science Through an Ethnoscience E-module : A Case Study in Surakarta, Indonesia - Prabowo, Doni Wahyu; Bramastia, Bramastia; Sarwanto, Sarwanto; Cohen, James (Jurnal Pendidikan Sains Indonesia, 2024)
Based on its history, Surakarta is one of the oldest cities in Indonesia which has various cultural heritage and indigenous knowledge. These can be integrated as ethnoscience-based science learning in schools. One of indigenous knowledge in Surakarta is Keris, a sharp weapon with a curved or straight blade. This paper attempts to explore students understanding in connecting indigenous knowledge with science through ethnoscience e-module in science learning. This covers students understanding about local indigenous knowledge and its scientific explanation. This mixed case study contains a combination of quantitative and qualitative approaches. Quantitative data is obtained based on the questionnaire results of 125 students from 5 schools in Surakarta, while qualitative data is in the form of in-depth interviews of 5 students. The questionnaire results show significant impacts in increasing students understanding about local indigenous knowledge and its connection with scientific explanation. Then, the in-depth interviews indicates that students are happy and have interest in learning with ethnoscience. This paper also contributes to cultural preservation by providing indigenous knowledge as well as scientific understanding by linking culture with science.